2017
DOI: 10.1002/14651858.cd004022.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low sodium diet versus high sodium diet on blood pressure, renin, aldosterone, catecholamines, cholesterol, and triglyceride

Abstract: Sodium reduction from an average high usual sodium intake level (201 mmol/day) to an average level of 66 mmol/day, which is below the recommended upper level of 100 mmol/day (5.8 g salt), resulted in a decrease in SBP/DBP of 1/0 mmHg in white participants with normotension and a decrease in SBP/DBP of 5.5/2.9 mmHg in white participants with hypertension. A few studies showed that these effects in black and Asian populations were greater. The effects on hormones and lipids were similar in people with normotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(162 citation statements)
references
References 227 publications
8
136
0
11
Order By: Relevance
“…Although clinical trials have reported a decrease in blood pressure with a reduction in sodium intake,8 many prospective cohort studies have reported a J-shaped association of sodium intake and cardiovascular disease or mortality,10111213141516 with an increased risk emerging at sodium intakes <2.7 g/day and >5 g/day 10. The increased cardiovascular risk associated with high sodium intake seems to be especially in those with hypertension,17 whereas the increased risk associated with low sodium intake might be mediated through activation of physiological systems to conserve sodium (eg, renin-angiotensin-aldosterone system) 18. In contrast, the association of potassium intake with blood pressure and cardiovascular disease is consistent, with a linear reduction in blood pressure and cardiovascular risk with increasing potassium intake reported in most studies 9.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical trials have reported a decrease in blood pressure with a reduction in sodium intake,8 many prospective cohort studies have reported a J-shaped association of sodium intake and cardiovascular disease or mortality,10111213141516 with an increased risk emerging at sodium intakes <2.7 g/day and >5 g/day 10. The increased cardiovascular risk associated with high sodium intake seems to be especially in those with hypertension,17 whereas the increased risk associated with low sodium intake might be mediated through activation of physiological systems to conserve sodium (eg, renin-angiotensin-aldosterone system) 18. In contrast, the association of potassium intake with blood pressure and cardiovascular disease is consistent, with a linear reduction in blood pressure and cardiovascular risk with increasing potassium intake reported in most studies 9.…”
Section: Introductionmentioning
confidence: 99%
“…A study published by Graudal et al compared the effects of a low and high sodium diet. In the group of individuals on a sodium-controlled diet, a drop in BP (by 3% in hypertensive patients) was accompanied by increased levels of renin, aldosterone, noradrenaline, adrenaline, cholesterol by 2.5% and triglyceride by 7% [33]. Fig.…”
Section: Treatment Of Resistant Hypertensionmentioning
confidence: 87%
“…20 A number of possible mechanisms have been proposed for the association, including that lower sodium intake decreases leptin, which reduces abdominal fat cells, resulting in lower adiposity and insulin resistance. 26 A second proposition is that lower intake of dietary sodium modifies the expression of glucose transporter type-4 protein in adipocytes and may therefore improve insulin sensitivity. 27 A final proposed mechanism is that low sodium intake alters the level of angiotensin II, which regulates insulin activity.…”
Section: Discussionmentioning
confidence: 99%